The quality perceived in Emergency departments between patients and caregivers according to waiting time: a cross sectional multicenter study - Lupo, Roberto; Marchisio, Daniele; Busto, Francesca; Lezzi, Alessia; Zacchino, Simone; Rea, Teresa; Botti, Stefano; Rubbi, Ivan; Artioli, Giovanna; De Mitri, Ornella; Calabrò, Antonino; Conte, Luana; et al. (Acta Biomedica Atenei Parmensis, 2024)
Background and aim of the work: In recent years there has been a growing interest in risk management and the quality of services offered to the user in healthcare services, a concept that has undergone a series of changes following its diffusion, entering into all productive processes, especially in Emergency Departments (EDs). The present study aims to assess which indicators invalidate in the perception of the quality of care received by the sample, as well as how it varies according to differences in the characteristics of patients and caregivers. Methods: A multicenter, cross sectional observational study was conducted through the snowball sampling method. A link was created thanks to the Google forms platform and disseminated through the social platforms of Triage Training Group and of the University of Turin, Italy. Results: A total of 624 participants agreed to participate in this study, specifically, 390 were patients and 234 were caregivers. The quality level perception was assessed by referring to the first phases of the ED. Most of the patients interviewed considered information received at the triage phase as insufficient (15.9%) and very insufficient (5.3%), (p=0.008). Conclusions: Emerged data suggested a degree of user dissatisfaction, specifically in the triage and waiting phases, which aimed to strengthen the motivations to implement organizational solutions to decrease waiting times, not just increase a subjective feeling of satisfaction.